2022
DOI: 10.1021/acs.iecr.2c03080
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Process Safety Assessment Using Adaptive Bayesian Network with Loss Function

Abstract: Fault detection and diagnosis (FDD) is crucial for dynamic process safety analysis. Integrated with failure prediction models, it enables us to realize how a deviation in process variable(s) can affect system safety (measured as risk). This work aims to overcome the challenges of nonlinear, non-Gaussian, and multimodal behavior of the processing systems to detect abnormal process operations, predict dynamic operational risk, and diagnose root cause of the abnormal situation. A methodology is proposed here by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Twenty distinct known and unknown faults (IDV-1 to IDV20) have been studied in several investigations. [66,[68][69][70] The proposed robust ANN model has been examined for detecting the step fault (IDV-1) and the sticking fault (IDV-14) of the TE process using 500 normal and 500 faulty samples. The real and mislabelled data of IDV-1 and IDV-14 faults of the TE process have been presented in Figures 7 and 8, respectively.…”
Section: Fault Detection In the Te Process Using The Robust Ann Modelmentioning
confidence: 99%
“…Twenty distinct known and unknown faults (IDV-1 to IDV20) have been studied in several investigations. [66,[68][69][70] The proposed robust ANN model has been examined for detecting the step fault (IDV-1) and the sticking fault (IDV-14) of the TE process using 500 normal and 500 faulty samples. The real and mislabelled data of IDV-1 and IDV-14 faults of the TE process have been presented in Figures 7 and 8, respectively.…”
Section: Fault Detection In the Te Process Using The Robust Ann Modelmentioning
confidence: 99%
“…Generally speaking, these cannot proactively predict failure unless the initiating event happens. Efforts are ongoing on how to integrate data‐driven FDD models with these logical failure prediction models for dynamic risk monitoring and early failure prognosis (FP) 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…Efforts are ongoing on how to integrate data-driven FDD models with these logical failure prediction models for dynamic risk monitoring and early failure prognosis (FP). 20,21 Although data-driven methods are widely used to describe and validate anecdotes of accident prevention, there is a lack of understanding among early Chemical Engineering students (many of whom will be future process safety torchbearers) about how these methods can be integrated with the commonly used software (e.g., Aspen HYSYS). Dynamic process simulation can improve safety and reliability.…”
mentioning
confidence: 99%
“…In recent years, data-knowledge-driven approaches have attracted increasing attention and interest in academia and have achieved the broad applications in solving various engineering problems such as system modeling and control, process monitoring, fault diagnosis, and so on. Specifically, as an important artificial intelligence (AI) technique, the Bayesian network (BN) is a type of probabilistic graphical model that is capable of effectively integrating data and knowledge to simulate human reasoning. It represents the causal relations of variables by a directed acyclic graph, and so it has better interpretability than other AI methods. , Owing to the advantages in interpretability, probabilistic modeling, and dealing with data uncertainties, BNs have been widely applied to a variety of industrial systems and processes in different areas to successfully solve problems such as process monitoring, fault diagnosis, prognosis, risk assessment, decision making, etc. ,, However, the BN-based PQC studies in the pharmaceutical field are rarely reported. Because of its significant advantages and application potential, we attempt to utilize BN for PQC (or operational adjustment) tasks for the first time.…”
Section: Introductionmentioning
confidence: 99%